Study of lifestyle disease risk factors among school going adolescents of urban Bareilly, Uttar Pradesh, India - Mahmood, Syed Esam; Bilal Khan, Khan Mohammad; Agrawal, Ajay Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: The rising burden of preventable risk factors for life style diseases among adolescents is a major public health challenge worldwide. This study was conducted to identify the preventable risk factors for life style diseases in adolescents. Methods:This cross-sectional study was undertaken amongst adolescents studying in senior secondary schools of urban Bareilly using purposive sampling. The students were surveyed through a self administered questionnaire after taking consent from their principal. Dietary practices, physical activity, tobacco and alcohol use were assessed. Blood pressure and body mass index were measured. The data was analyzed using SPSS software. Results: Out of 250 participants, majority (62.0%) were males. Only 4.8% were currently using tobacco while 3.2% respondents admitted having consumed alcohol in last 30 days. Only 28.8% did brisk walking and cycling for at least 30 minutes continuously thrice a week. Nearly 22.4% were involved in moderate intensity sports while 20.4% in vigorous intensity sports. Nearly 5.6% regularly practiced yoga. About 52.4% were non vegetarians. Nearly 70.8% consumed adverse food items such as fried food, cheese, butter, meat, egg, sweetened drinks, pizza, burger, bakery items, pickles and sauces daily. Only 64% consumed fruits while 75.6% consumed vegetables for at least three days in a typical week. Also 24.4% added extra salt to cooked food items. The overall prevalence of hypertension was 12.0%. About 64.4% were underweight, while 7.6% were overweight. Conclusions:Adoption of healthy lifestyles by all adolescents is critical for the prevention of lifestyle diseases.